Modal testing of an isolated overpass bridge in its construction stages - Fuat Aras (The Baltic Journal of Road and Bridge Engineering)
This study presents the application of ambient vibration survey based dynamic testing on an isolated, precast and pre-stressed overpass bridge during and after its construction. In the studied three-bay bridge, the girders are located on the elastomeric bearings carried by two abutments and two internal piers. The first modal testing is performed after the placement of the girders on the elastomeric bearings and dynamic properties of the uncompleted bridge are determined. After the completion of all construction works and the opening of the overpass to human traffic, the modal testing is repeated to obtain the dynamic properties of the final structure. The dynamic properties obtained in both analyses are used to interpret the effects of the performed works between two modal testing. Moreover, the structural behaviour of isolated, precast and pre-stressed bridges is evaluated in detail.